INTEGRATING ARTIFICIAL INTELLIGENCE (AI) IN ESP INSTRUCTION: ENHANCING DIGITAL BUSINESS ENGLISH LITERACY AMONG ECONOMIC EDUCATION STUDENTS - Lodya Sesriyani (Universitas Bina Bangsa Getsempena, 2026)
In the era of digital transformation, the integration of Artificial Intelligence (AI) has become a crucial necessity in higher education. This study aims to analyze the utilization of AI-based tools (such as ChatGPT, Perplexity, and Grammarly) in enhancing business correspondence writing skills and English-language economic data analysis among fourth-semester students of the Economic Education Study Program at Universitas Pamulang. Adopting a Classroom Action Research (CAR) method combined with perception surveys, this study involved an experimental group implementing AI-assisted Project-Based Learning (PjBL). Data were collected through pre-tests and post-tests of business writing proficiency, as well as Likert-scale questionnaires to measure students' learning autonomy. The findings indicate that the directed use of AI significantly improves the accuracy of economic terminology and the efficiency of drafting business reports in English. Furthermore, students demonstrated a high increase in motivation as the instructional materials were more aligned with Industry 4.0 trends. However, the study also identifies challenges regarding academic ethics and over-reliance on digital tools. This research concludes that AI literacy must be integrated into the English for Specific Purposes (ESP) curriculum at Universitas Pamulang to ensure students possess a competitive edge in the global labor market.